2014
DOI: 10.3389/fmicb.2014.00443
|View full text |Cite
|
Sign up to set email alerts
|

Optical and dielectric sensors based on antimicrobial peptides for microorganism diagnosis

Abstract: Antimicrobial peptides (AMPs) are natural compounds isolated from a wide variety of organisms that include microorganisms, insects, amphibians, plants, and humans. These biomolecules are considered as part of the innate immune system and are known as natural antibiotics, presenting a broad spectrum of activities against bacteria, fungi, and/or viruses. Technological innovations have enabled AMPs to be utilized for the development of novel biodetection devices. Advances in nanotechnology, such as the synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 89 publications
(129 reference statements)
1
16
0
Order By: Relevance
“…The LoD was found to be as low as 3.5·10 1 CFU· mL -1 , which is comparable with or better than other detection limit values previously reported for direct label-free bacterial detection (Basu et al, 2014;Dweik et al, 2012;EscamillaGómez et al, 2009;Li et al, 2014;Silva et al, 2014;Varshney and Li, 2007).…”
Section: Sensitivity Of the System In Kcl Solutionsupporting
confidence: 84%
See 2 more Smart Citations
“…The LoD was found to be as low as 3.5·10 1 CFU· mL -1 , which is comparable with or better than other detection limit values previously reported for direct label-free bacterial detection (Basu et al, 2014;Dweik et al, 2012;EscamillaGómez et al, 2009;Li et al, 2014;Silva et al, 2014;Varshney and Li, 2007).…”
Section: Sensitivity Of the System In Kcl Solutionsupporting
confidence: 84%
“…This sensor was used to selectively detect E. coli O157:H7, and showed a limit of detection (LoD) of 10 3 colony forming units (CFU)·mL -1 . In another recent study, two synthetic AMPs with species-specific targeting (C16G2cys and G10KHc) were immobilized onto gold electrode surfaces to detect Streptococcus mutans (S. mutans) and Pseudomonas aeruginosa (Lillehoj et al, 2014), displaying LoDs of 10 5 CFU·mL -1 for both strains (Silva et al, 2014). Although those strategies have demonstrated good sensitivity for bacterial detection, some of them require extensive sample preparation and multiple assay steps prior to detection (Li et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many amphibians secrete a wide range of antimicrobial peptides (AMPs) and other biologically active compounds to protect the skin from bacterial infection 1, 2 and these peptides have the potential for further commercial development, including roles as anti-infective, anticancer, antiviral and anti-diabetic agents [3][4][5][6] . For example, maximin H5 (MH5) is an anionic peptide that belongs to a family of AMPs identified in the skin secretions of the Chinese red belly toad, Bombina maxima 7 and in the brain of both B. maxima and other toads of the same genus 8 .…”
mentioning
confidence: 99%
“…A general common feature of AMPs is their wide spectrum in terms of target neutralization (specific to Gram-negative, Grampositive or both, for instance). Interestingly, although they have strong affinity to bacterial membranes, their potential use as probes for biosensing applications is quite recent (Silva et al 2014). In the specific case of SA interactions with AMPs, it has been shown that this pathogen developed, during evolution, several mechanisms such as alteration of the overall negative charge of their membrane (thus decreasing the natural electrostatic interaction of most positively charged AMPs), or secretion of a cationic exopolysaccharide or proteases acting on AMPs (Joo and Otto 2015).…”
Section: Aptamersmentioning
confidence: 99%